Climate‐change vulnerability assessments of natural resources in U.S. National Parks. Issue 7 (18th May 2022) - Michalak, Julia L.; Lawler, Joshua J.; Gross, John E.; Agne, Michelle C.; Emmet, Robert L.; Hsu, Hsin‐Wu; Griffey, Vivian
Abstract: Climate change poses significant challenges to protected area management globally. Anticipatory climate adaptation planning relies on vulnerability assessments that identify parks and resources at risk from climate change and associated vulnerability drivers. However, there is currently little understanding of where and how protected area assessments have been conducted and what assessment approaches best inform park management. To address this knowledge gap, we systematically evaluated climate‐change vulnerability assessments of natural resources in U.S. National Parks. We categorized the spatial scale, resources, methods, and handling of uncertainty for each assessment and mapped which parks have assessments and for what resources. We found that a few broad‐scale assessments provide baseline information—primarily regarding physical climate change exposure—for all parks and can support regional to national decisions. However, finer‐scale assessments are required to inform decisions for individual or small groups of parks. Only 10% of parks had park‐specific assessments describing key climate impacts and identifying priority resource vulnerabilities, and 37% lacked any regional or park‐specific assessments. We identify assessment approaches that match the scale and objectives of different protected area management decisions and recommend a multi‐scaled approach to implementing assessments to meet the information needs of a large, protected area network like the National Park system. Abstract : We reviewed climate‐change vulnerability assessments of natural resources in U.S. National Parks to identify common approaches and resources evaluated. Assessments varied widely in spatial scale, conceptual scope, and level of detail. We found that designing assessments to match the scale and objectives of protected‐area management decisions is essential and describe a multi‐scaled assessment approach to meet the information needs of a large protected‐area network like the National Park system.